Optical anisotropy of pristine and reduced V2O5(010) - Brian Walls; Oisín Murtagh; Chris M. Smith; Daragh Mullarkey; Dmitry Shulyatev; Karsten Fleischer; Ainur Zhussupbekova; Igor V. Shvets (Scientific Reports)
Abstract The optical anisotropy of pristine and reduced single crystalline (010) orientated $$\hbox {V}_{2}\hbox {O}_{5}$$ is presented. The reduction of $$\hbox {V}_{2}\hbox {O}_{5}$$ is complex due to the abundance of V-O phases, strong dependence on the reducing conditions and multitude of reduction pathways. Different phases close in stoichiometry can exhibit drastically different electronic and optical properties. Reflectance anisotropy spectroscopy (RAS) provides a non-destructive optical probe that can be employed in real-time to monitor changes in thin films. Pristine $$\hbox {V}_{2}\hbox {O}_{5}$$ (010) exhibits strong anisotropy with significant features beyond the optical bandgap of 2.5 eV. Axially resolved optical constants, extracted using ellipsometry, facilitate the calculation of the RAS which is in excellent agreement with the experimental data. Vacuum annealing has been performed at four different temperatures and X-ray Diffraction and RAS have been conducted after each anneal. Depending on the anneal temperature, different phases are introduced into the $$\hbox {V}_{2}\hbox {O}_{5}$$ crystal including $$\hbox {V}_{4}\hbox {O}_{9}$$ , $$\hbox {V}_{6}\hbox {O}_{13}$$ and $$\hbox {VO}_{2}$$ . Spectral features of each of these phases are identified. $$\hbox {V}_{6}\hbox {O}_{13}$$ is understood in terms of the axially resolved optical constants from the literature, while isotropic $$\hbox {VO}_{2}$$ modifies the total reflection once it undergoes its semiconductor-to-metal phase transition at 340 K. This understanding of the optical response of the ideal single crystal facilitates applying RAS to monitor the growth and changes of $$\hbox {V}_{2}\hbox {O}_{5}$$ thin films in real time.